Penanggulangan Sedimentasi Pada Bendungan Plara Kabupaten Sumbawa - Didin Najimuddin; Israjunna Israjunna; Ady Purnama (Indonesian Journal of Applied Science and Technology, 2020)
Problems with the Plara Dam include the amount of sedimentation so that the water flow retained in the dam is not optimal. One effort to overcome sedimentation is to normalize sedimentation. The availability and need of water do not always meet the needs of life, both for humans, animals and plants. This happens because there is no balance between availability and water demand. Erosion and sedimentation are a series of processes related to the process of weathering, releasing, transporting and settling soil/crust material. With erosion in the watershed and the amount of sedimentation observed in the river flow at the bottom of the catchment is closely related to the hydrological system of the watershed. Rain as input in the hydrological system after experiencing the process will produce output in the form of flowrate and sediment load. The purpose of this study was to determine the volume of sedimentation in the Plara Dam. The method used in this research is to take primary and secondary data. The results of this study are the smallest rainfall intensity occurred in 2011 amounted to 1051.5 mm/sec and the highest occurred in 2016 amounted to 1734.7 mm/sec. Sedimentation volume occurred in the P19 - P20 area of 12129.32 m3 with total sedimentation of the P1-P20 area of 338588.93 m3.